The classification of distances and groupings of various musical elements through three methods of evaluation of similarities developed in cognitive psychology: Contrast Model, Structural Alignment and Transformation - Lázzari, Ednilson José Toledo; Netto, Amilcar Zani (Seven Editora, 2024)
The study aims to use three methods of evaluation of similarities developed in cognitive psychology in the classification of distances and groupings of diatonic chords in major and minor keys, taking into account the four tonal scales (Ionian, Aeolian, Harmonic Minor and Melodic Minor), of the twenty-four tonalities, also taking into account the four tonal scales, of the forty-eight series of Alban Berg’s Violin Concerto and of some sets representing scales in music theory. The methods employed are: the Contrast Model, which weights the common and distinct characteristics between the objects compared (Tversky 1977); the Structural Alignment, which classifies similarities by distinguishing between two types of differences and two types of commonalities (Gentner; Markman 1995, 1997; Goldstone 1994; Markman; Gentner 1990, 1993a, 1993b, 1993c, 1996); and Transformation, which evaluates similarities through the number of operations required to transform one object into another (Chater; Hahn 1997; Hahn; Chater; Richardson 2003; Hahn; Richardson; Chater 2001). DOI:https://doi.org/10.56238/sevened2024.010-010